The ring two - Nakata, Hideo, 1961-; Watts, Naomi, 1968-; Baker, Simon, 1969-; Dorfman, David, 1993-; Perkins, Elizabeth, 1960-; Cole, Gary, 1956-; Beristain, Gabriel; Lohner, Henning; Tillman, Martin; Dreamworks Pictures; Universal Studios Home Entertainment (Firm) ([Universal City, Calif.] : DreamWorks : Universal Studios Home Entertainment, 2005)
Six months after the frightening rampage and the cursed videotape that left so much death and terror, Rachel and her son start a new life in a small Oregon town. But when a crime scene includes an unmarked tape, she knows the violence has not ended.
Title from container.
Cinematographer, Gabriel Beristain ; editor, Michael N. Knue ; music, Henning Lohner, Martin Tillman ; costume designer, Wendy Chuck ; production designer, James D. Bissell.
Naomi Watts, Simon Baker, David Dorfman, Elizabeth Perkins, Gary Cole, Sissy Spacek, Ryan Merriman, Emily VanCamp, Kelly Overton, James Lesure.
MPAA rating: Not rated.
DVD, region 1, 1.85:1 presentation; Dolby Digital 5.1 surround, Dolby Digital 2.0 stereo.
English dialogue with optional English, French or Spanish subtitles; closed-captioned.
Keywords: Video tapes -- Drama; Death -- Drama; Feature films; Horror films; Video recordings for the hearing impaired